The occurrences, characteristics, and implications of chaotic rocks (accretionary rocks) within the Trans-Saharan orogenic belt in Nigeria - Nchekwube D. Nweke; Emmanuel N. Ugwuonah; Leonard N. Onuba; Johnbosco C. Egbueri (Discover Geoscience)
Abstract The present research paper reveals the occurrences of metachaotic rocks/accretionary sediments (mélange) in Igarra, southwest Nigeria. These metachaotic rocks are associated with schistose, marble, pegmatite, granitoid, and gneissose units. The mineral assemblage of the surrounding rocks shows garnet, biotite, staurolite, quartz, and chlorite assemblage, which suggest that the rocks were metamorphosed to the epidote–amphibolite facies grade. The chaotic rocks were classified into four groups based on major differences in color, grain size distribution, and stratigraphic and structural characteristics of observed blocks and matrices surrounding them. Group I metachaotic rocks are melanocratic in color, and form pockets of coarse lineation. They are highly deformed with mullions, rodding structures, and burrow-like cavities and show quartzite veins. Group II occurs as a leucocratic to melanocratic mixture of meta-siltstone and metapelite with greenish rock fragments trapped within the meta-siltstone layers. This unit has a cover of meta-siltstone layers occurring in pockets as striations forming mullion and rodding structures as well as ripple-like lineation. Group III metachaotic rocks occur as multiple benches of different strata tilted between 70 and 80º, with mild folding and  burrow-like cavities at the base and well-preserved sedimentary structures. In Group IV, there are evidences of pre-metamorphic soft sediment deformational structures that are well-preserved in the metachaotic rocks, with discontinuous blocks of different units trapped within mixtures of metapelite and meta-siltstone. In this group, micro-faults and quartzite veins are scattered within the rocks. Meta-siltstone occurs as horizontal and vertical layers and web-like structures showing dendritic patterns. Overall, the field and petrographic characteristics suggest the Igarra metachaotic rocks are tectonic in origin and may have been formed within the trench basin of an outer accretionary complex.